A socio‐emotional analysis of technology use by people with intellectual disabilities. Issue 2 (22nd November 2020) - Setchell, J.; Barlott, T.; Torres, M.
Abstract: Background: Access to information and communication technologies (ICTs) is often thought to enhance the lives of people with intellectual disabilities (ID) and is considered an important aspect of digital inclusion. However, inclusion practices often fail to address societal inequalities that lead to and sustain exclusion. The aim of this research was to enhance understandings of the relationships people with ID form with technology by critically analysing the underlying assumptions of inclusion practices. Method: We employed a post‐qualitative approach to reanalyse previously collected data from face‐to‐face interviews with 10 Australian adults with ID who attended a community literacy programme about their technology use in their daily lives. Two of social theorist Sara Ahmed's key concepts were used to analyse these data: (1) 'stickiness' of emotions, where certain (socially dominant) emotions are considered to attach to objects over time (e.g. mobile phone use is normal/good) and (2) 'fit' between people and objects, where there is a sense of comfort when objects are designed for people like you – those outside the 'norm' experience discomfort and a sense of being 'othered' in their interactions with such objects which do not fit them. Results: Our analysis identified how people with ID often attributed positive feelings to technology even when they had seemingly negative interactions with their devices (e.g. they could not use certain features, caregivers acted as gatekeepers to access). The positive associations were likely the outcome of implicitly held understandings that society highly values technology (Ahmed's stickiness of emotions). Although some participants accessed technology without difficulty, others experienced discomfort due to difficulties using devices that were not designed for them (Ahmed's fit between people and objects). Importantly, some participants had access to technology and the technical skill to use ICTs, but other factors, such as not having many friends, impacted their ability to use their devices in meaningful ways. Conclusion: Our analysis suggests that digital inclusion practices focused on providing access to technology may unintentionally harm in ways that are not immediately apparent when working with people with ID. Harms might include further marginalisation or 'othering' of people with ID. It is important to recognise that well‐meaning attempts to encourage use of ICTs may be counterproductive if they lead to experiences of marginalisation. To avoid this, inclusion practices could focus beyond access to devices, and the ability to use them, to include considerations of the multiple socio‐emotional effects. What is a good fit is not entirely predeterminable, exploration of the possibilities for what will work well for any individual requires experimentation and creativity, and a careful attention to unintended effects. Beyond this, the development of new technology should consider how to diversify devices that often fail to fit people with disabilities.